2002
DOI: 10.1081/cnv-120002155
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Alterations in Cancer

Abstract: A number of studies have demonstrated the presence of mitochondrial DNA (mtDNA) mutations in cancer cells. In this article, we review mitochondrial genomic aberrations reported in solid tumors of the breast, colon, stomach, liver, kidney, bladder, head/neck, and lung. The tantalizing association of tumors with mtDNA mutations implicates these mutations in the process of carcinogenesis. Alterations in expression of mtDNA transcripts in a variety of cancer types are also reviewed. In solid tumors, elevated expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(121 citation statements)
references
References 93 publications
3
113
0
2
Order By: Relevance
“…Mutations in mtDNA can cause impairment of oxidative phosphorylation and increase ROS production which in turn accelerates the DNA mutation rate (Pang et al, 2008). It is reported that the mutation frequency in mtDNA is about 10-to 20-fold greater as compared to nuclear DNA (Copeland et al, 2002). Mitochondrial DNA mutations are present in both coding and non-coding regions and most of them appeared to be homoplasmic in nature (Chatterjee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in mtDNA can cause impairment of oxidative phosphorylation and increase ROS production which in turn accelerates the DNA mutation rate (Pang et al, 2008). It is reported that the mutation frequency in mtDNA is about 10-to 20-fold greater as compared to nuclear DNA (Copeland et al, 2002). Mitochondrial DNA mutations are present in both coding and non-coding regions and most of them appeared to be homoplasmic in nature (Chatterjee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative aberrations of mtDNA, such as mutations, have been found in solid tumours, such as colon, stomach, liver, kidney, bladder, prostate, skin and lung cancer (Copeland et al 2002;Penta et al 2001), and in haematological malignancies, such as leukaemia and lymphoma (Fontenay et al 2006). Quantitative aberrations of mtDNA have been observed in various sample types from patients with cancers (Mambo et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The role of mitochondria-derived ROS has also been implicated in a proposed vicious cycle linking mtDNA mutation in tumors. On the one hand, a burst of ROS production from mitochondria would favour oxidative dependent mitochondrial mutagenesis and hence promote tumorigenesis [37]; While on the other hand, mutation of mtDNA in the respiratory chain components could commence a cascade of events leading to an increase in electron leakage and ROS over-generation in the process of malignant transformation and tumor progression [38,39]. Several mtDNA mutations have been found in breast tumors [40], and the presence of mtDNA mutations in breast cancer cells is consistent with the intrinsic susceptibility of mtDNA to damage and persistent oxidative stress [41].…”
Section: Altered Mitochondrial Machinerymentioning
confidence: 99%